2010
DOI: 10.1146/annurev-genet-102209-163432
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Control of Global Gene Expression Patterns

Abstract: An internal time-keeping mechanism has been observed in almost every organism studied from archaea to humans. This circadian clock provides a competitive advantage in fitness and survival (18, 30, 95, 129, 137). Researchers have uncovered the molecular composition of this internal clock by combining enzymology, molecular biology, genetics, and modeling approaches. However, understanding the mechanistic link between the clock and output responses has been elusive. In three model organisms, Arabidopsis thaliana,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
227
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(234 citation statements)
references
References 143 publications
7
227
0
Order By: Relevance
“…Our study revealed a positive feedback loop consisting of LWD1 and PRR9 in the Arabidopsis circadian clock (Figure 9). Positive and negative feedback loops exist in the circadian clock of many model organisms (for review, see Doherty and Kay, 2010). Negative feedback loops can contribute to the clock's function in building the 24-h oscillation.…”
Section: Discussion Lwd1 and Prr9 Constitute A Positive Feedback Loopmentioning
confidence: 99%
“…Our study revealed a positive feedback loop consisting of LWD1 and PRR9 in the Arabidopsis circadian clock (Figure 9). Positive and negative feedback loops exist in the circadian clock of many model organisms (for review, see Doherty and Kay, 2010). Negative feedback loops can contribute to the clock's function in building the 24-h oscillation.…”
Section: Discussion Lwd1 and Prr9 Constitute A Positive Feedback Loopmentioning
confidence: 99%
“…Researchers have devised and evaluated many methods (see a short list in Doherty and Kay, 2010), each with strengths and weaknesses (e.g. Deckard et al, 2013;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The circadian clockwork allows plants to anticipate environmental changes and adapt their activity to the most appropriate time of day (18). In Arabidopsis thaliana, the core of the oscillator is composed of morning-and evening-expressed components that regulate their expression in a highly complex network of interconnections (19). The transcription factors CCA1 (CIRCADIAN CLOCK ASSOCIATED 1) (20), LHY (LATE ELONGATED HYPOCOTYL) (21), and the PSEUDO-RESPONSE REGU-LATOR (PRR) proteins (PRR9, -7, and -5) (22) have peak phases of expression during the day, whereas TOC1 (TIMING OF CAB EXPRESSION 1 or PRR1) (23,24), GI (GIGANTEA) (25,26), and the members of the Evening Complex (EC) (27), all have evening peak-phase oscillations.…”
mentioning
confidence: 99%